Global profile of individuals undergoing total knee replacement through the PROGRESS-PLUS equity lens: Protocol for a systematic review - Marisa Coetzee; Amanda M. Clifford; Jacobus D. Jordaan; Quinette A. Louw (AOSIS, 2022)
Background: Osteoarthritis (OA) is a heterogenous degenerative disorder often causing destructive joint changes with severe pain and functional disability. Modifiable and non-modifiable risk factors, social context and psychological factors influence the development and progression of the disease. Total knee replacement (TKR) aims at reducing pain and improving function and is more successful with pre-operative and post-operative rehabilitation. However, most international research on rehabilitation interventions is conducted in high income contexts. Objective: The aim of our systematic review is to gain an overview of the demographic and social profiles of adults undergoing TKR for primary knee OA in lower, middle- and high-income countries through a health equity lens to inform the translation of intervention research in local contexts. Methods: A systematic review will be conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Eligibility criteria include observational studies and grey literature (theses) since the beginning of the databases reporting on demographic data of adults awaiting or undergoing TKR surgery. The PROGRESS-Plus framework will be used to describe equity elements. Results: A narrative summary and description of the global profile of individuals undergoing total knee replacement for osteoarthritis. Conclusion: A snapshot of the global demographic and social profile of individuals receiving TKR for primary knee OA through an equity lens will shed light on the similarities and differences between individuals from different contexts. Global demographic profile information may inform or assist in the development of translational strategies for evidence-based rehabilitation. Clinical implications: Translation of existing rehabilitation interventions to local contexts could improve pre-operative and post-operative outcomes for individuals on our surgical waiting lists.